(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Based on the results of observations and interviews at SDN Karangwidoro 1 and SDN Karangwidoro 2, students’ basic movement patterns are very lacking. Since 2017, SDN Karangwidoro 2 has not had a sports teacher, so students’ gross motor skills are lacking. Meanwhile, at SDN Karangwidoro 1, there is a lack of game innovation. This research aims to develop a phase B basic pattern game that can be used at the elementary school level, especially in Karangwidoro Village. This game is designed to improve students’ gross motor skills and support the physical and mental development of children at the elementary school level. The development process was carried out using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which includes needs analysis, game design, prototype development, implementation in elementary schools, and evaluation of the game’s effectiveness. The UI test subjects used in this research were 42 students in grades 3 and 4 at an elementary school in Karangwidoro village. The results of the game expert validation showed 93%, learning expert validation 97%, media expert validation 95% and field trial results 93%. The results of the research show that the basic movement pattern game in Phase B, which was developed, was able to improve students’ movement skills in the aspects of coordination, balance, agility, and physical strength. Thus, it is hoped that this game can be an effective means of supporting basic movement learning in elementary schools in Karangwidoro Village and can be used as a reference for developing a more innovative and interesting physical curriculum.